2023
DOI: 10.3389/fmed.2023.1157389
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green fluorescence angiography decreases the risk of anastomotic leakage after rectal cancer surgery: a systematic review and meta-analysis

Abstract: BackgroundAnastomotic leakage is a serious complication after rectal cancer resection. Intraoperative use of indocyanine green fluorescence angiography (ICGFA) can help prevent anastomotic leakage, but its use is controversial. We conducted a systematic review and meta-analysis to determine the efficacy of ICGFA in reducing anastomotic leakage.MethodsRelevant data and research published until September 30, 2022, was retrieved from the PubMed, Embase, and Cochrane Library databases, and the difference in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Two meta-analyses, Safiejko et al (three RCTs and 29 cohort studies) and Xia et al (three RCTs and 19 cohort studies), specifically assessed the benefits of ICG-FA which also revealed a reduction in anastomotic leak rate. 71,72…”
Section: Perfusion Assessmentmentioning
confidence: 99%
“…Two meta-analyses, Safiejko et al (three RCTs and 29 cohort studies) and Xia et al (three RCTs and 19 cohort studies), specifically assessed the benefits of ICG-FA which also revealed a reduction in anastomotic leak rate. 71,72…”
Section: Perfusion Assessmentmentioning
confidence: 99%